2012
DOI: 10.1016/j.phytol.2012.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of tuberospironine A, a novel croomine derivative from Stemona tuberosa Lour.

Abstract: A novel croomine derivative, tuberospironine A (3-epi-tuberospironine) was isolated from the root extracts of Stemona tuberosa Lour. found growing on Seram Island, Moluccas Province, Indonesia. The structure of this novel alkaloid, with unprecedented configuration at C-3 for a croomine derivative, was determined from interpretation of its NMR spectroscopic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The crude alkaloid was separated using column chromatography under silica gel as stationary phase and DCM-methanol as mobile phase with polarity gradient elution. The alkaloids were purified using preparative chromatography to give tuberostemonine, croomine, and epi -croomine ( epi -10-hydroxycroomine or 3- epi -tuberospironine A) [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The crude alkaloid was separated using column chromatography under silica gel as stationary phase and DCM-methanol as mobile phase with polarity gradient elution. The alkaloids were purified using preparative chromatography to give tuberostemonine, croomine, and epi -croomine ( epi -10-hydroxycroomine or 3- epi -tuberospironine A) [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…collected from Seram Island, Moluccas Province, Indonesia (Figure 5). 72 Stemona-lactams R ( 137 ) with a hydroxy group at C10 was obtained from the roots of Stemona tuberosa (Figure 5). 26 Yuea et al 27 found 9 a - epi -tuberospironine ( 138 ) from the roots of Stemona tuberosa (Figure 5).…”
Section: Phytochemistrymentioning
confidence: 99%